(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the evolution of non-state educational institutions in the Republic of Uzbekistan from 1991 to 2024. It provides an in-depth analysis of the historical context, socio-economic factors, and the growing public demand for diverse educational opportunities. Drawing upon the Law “On Education,” the study highlights the rationale behind the establishment of private preschools, general secondary schools, and private higher education institutions. The article underscores the pivotal role of legislative reforms, public-private partnerships, and international cooperation in shaping the landscape of private education in Uzbekistan.